Effects of different resistance exercise intensity on mitochondrial DNA deletions in young athletes - Rahimi, R.; Saleh, Z.; Mousavi Beneh-Hoor, Z. (Medicina dello Sport, 2013)
Aim. The purpose of the present study was to examine the effect of resistance exercise (RE) with different intensities on mitochondrial DNA deletions including 4977-bp (mtDNA4977 deletion), 8.7 kb, 7.5 kb and 7.4 kb deletion in young athletes. Methods. Ten resistance-trained men (age: 21±2.30 year; weight: 74.71±8.73 kg; height: 175.14±5.95 cm) performed high intensity RE (4 sets of 5 exercises at 90% of 1RM with 3 min rest between sets) and moderate intensity RE (4 sets of 5 exercises at 75% of 1RM with 1 min rest between sets) on a separate occasion in a counterbalanced order. Blood samples were obtained before (Pre) and immediately after (Post) RE for analyzing mtDNA deletions in blood leucocytes by multiplex polymerase chain reaction (PCR). Results. The results indicated that 8.7 kb, 7.5 kb, 7.4 kb and mtDNA4977 deletion, were not evident in leucocytes at Pre and Post during both RE intensities. Conclusion. In conclusion, our findings showed that RE did not induce mtDNA deletions in resistance trained men, probably because of adaptations occurring owing to chronic resistance training.